Dietary Pattern Associated with Frailty: Results from Nutrition and Health Survey in Taiwan - Lo, Yen‐Li; Hsieh, Yao‐Te; Hsu, Li‐Lin; Chuang, Shao‐Yuan; Chang, Hsing‐Yi; Hsu, Chih‐Cheng; Chen, Ching‐Yu; Pan, Wen‐Harn (Journal of the American Geriatrics Society (JAGS), 2017)
Objectives To investigate whether dietary patterns are associated with frailty phenotypes in an elderly Taiwanese population. Design Cross‐sectional. Setting Nutrition and Health Survey in Taiwan (NAHSIT), 2014–2016. Participants Noninstitutionalized Taiwanese nationals aged 65 years and older enrolled in the NAHSIT (N = 923). Measurements Dietary intake was assessed using a 79‐item food‐frequency questionnaire (FFQ). Presence of 5 frailty phenotypes was determined using modified Fried criteria and are summed into a frailty score. Using data from the NAHSIT (2014–15), reduced rank regression was used to find a dietary pattern that explained maximal degree of variation of the frailty scores. Logistic regression models were used to estimate the association between frailty and dietary pattern. The findings were validated with data from 2016. Results The derived dietary pattern was characterized with a high consumption of fruit, nuts and seeds, tea, vegetables, whole grains, shellfish, milk, and fish. The prevalence of frailty was 7.8% and of prefrailty was 50.8%, defined using the modified Fried criteria. Using data from the NAHSIT (2014–15), the dietary pattern score showed an inverse dose‐response relationship with prevalence of frailty and pre‐frailty. Individuals in the second dietary pattern tertile were one‐third as likely to be frail as those in the first tertile (adjusted odds ratio (aOR) = 0.32, 95% confidence interval (CI) = 0.12−0.85), and those in the third tertile were 4% as likely to be frail as those in the first tertile (aOR = 0.04, 95% CI = 0.01−0.18). The dietary pattern score estimated using FFQ data from the NAHSIT 2016 was also significantly and inversely associated with frailty. Conclusion Individuals with a dietary pattern with more phytonutrient‐rich plant foods, tea, omega‐3‐rich deep‐sea fish, and other protein‐rich foods such as shellfish and milk had a reduced prevalence of frailty. Further research is necessary to confirm these findings and investigate whether related dietary interventions can reduce frailty in older adults.